2-Mercaptopyrimidine as an effective inhibitor for the corrosion of cold rolled steel in HNO3 solution. (April 2017) - Li, Xianghong; Deng, Shuduan; Lin, Tong; Xie, Xiaoguang; Du, Guanben
Graphical abstract: Highlights: MP acts an effective inhibitor in HNO3, but other pyrimidine derivatives are poor. MP is a mixed inhibitor, while mainly retards anodic reaction. EIS exhibit depressed capacitive loops whose diameters are increased with MP. The most active adsorption site is S atom for any MP molecular form. The adsorptive order is thiol-MP < thione-MP <  p -thiol-MP <  p -thione-MP. Abstract: The inhibition effect of five pyrimidine derivatives (2-chloropyrimidine, 2-hydroxypyrimidine, 2-bromopyrimidine, 2-aminopyrimidine, 2-mercaptopyrimidine) on the corrosion of cold rolled steel (CRS) in 0.1 M HNO3 solution was comparatively examined. 2-Mercaptopyrimidine (MP) was found to be an effective inhibitor with the inhibition efficiency as high as 99.1% at a low concentration 0.50 mM. But other four pyrimidine derivatives exhibited poor inhibitive ability. The addition of MP caused both anodic and cathodic curves to low current densities, and was found to significantly strengthen the impedance. Quantum chemical calculation and molecular dynamic simulation were performed to theoretically investigate the adsorption mechanism.